Marketing and Financial Management Strategies for Sustainability in Traditional Markets - Daulay, M. Safii Murad; Hasanah, Uswatun (Journal of Business and Economics Research (JBE), 2025)
This study explores marketing strategies and financial management in traditional market businesses, focusing on the Sukaramai Market in Medan, Indonesia. The research aims to address the challenges and opportunities faced by local traders in maintaining business sustainability while balancing marketing efforts and financial management. Data were collected through interviews with two shop owners specializing in textiles and clothing, with questions targeting operational practices, customer engagement strategies, revenue generation, and financial resource allocation. The respondents highlighted key marketing approaches, including direct promotions and customer loyalty programs, alongside financial practices such as managing initial capital, monthly turnover, and employee salaries. The study identifies significant challenges, such as competition with online platforms and fluctuating customer demand during seasonal periods. The analysis employs a qualitative approach to evaluate the effectiveness of these strategies and financial practices in achieving business stability. Preliminary findings indicate that while traders employ basic marketing and financial management techniques, limited digital adoption and informal accounting practices hinder their ability to scale operations effectively. The study emphasizes the need for integrating modern financial tools and e-commerce solutions to enhance competitiveness. These insights are relevant for policymakers and stakeholders aiming to support traditional market businesses in adapting to a rapidly changing economic landscape.